Terrestrial aeromagnetic survey of waste deposits: A pilot study in Gualeguaychú, Entre Ríos - Orgeira, M.J. (2004)
This paper presents the results of the application of terrestrial magnetometry in the study of waste deposits. The area chosen for the pilot study was located toward the south of the town of Gualeguaychú, in the southeastern Entre Rios province. This location was selected because it was known that operations were to cease and local authorities had an interest in verifying the presence of anomalies indicative of potentially dangerous environmental pollutants. Interpretation of the magnetic signal suggests that buried objects of high magnetic susceptibility are not large (smaller than containers of 1m in height). For that reason we discount the presence of drums of standard dimensions, the possible containers of toxic elements. The estimated depth of the objects of high susceptibility increases with the distance from the access road to the the area. © 2004 Asociación Geológica Argentina.